2009
DOI: 10.4049/jimmunol.0801463
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hepatic Invariant NKT Cells in Systemic/Local Inflammation and Mortality during Polymicrobial Septic Shock

Abstract: NKT cells have been described as innate regulatory cells because of their rapid response to conserved glycolipids presented on CD1d via their invariant TCR. However, little is known about the contribution of the hepatic NKT cell to the development of a local and/or systemic immune response to acute septic challenge (cecal ligation and puncture (CLP)). We found not only that mice deficient in invariant NKT cells (Jα18−/−) had a marked attenuation in CLP-induced mortality, but also exhibited an oblation of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
52
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 68 publications
11
52
0
2
Order By: Relevance
“…Several studies have demonstrated that NKT cells promote LPS-or cecal ligation and puncture (CLP)-induced sepsis in mice through the production of IFN-γ [8][9][10]. Consistent with these findings, two independent studies have demonstrated that treatment of C57BL/6 mice with anti-CD1d antibody enhances survival rates during CLP-induced sepsis [11,12], suggesting that NKT-cell-mediated promotion of sepsis depends on an interaction between CD1d and TCRs of NKT cells. In contrast, Etogo et al found that CD1d −/− mice did not exhibit improved survival in CLP-induced sepsis [10].…”
Section: Introductionsupporting
confidence: 68%
“…Several studies have demonstrated that NKT cells promote LPS-or cecal ligation and puncture (CLP)-induced sepsis in mice through the production of IFN-γ [8][9][10]. Consistent with these findings, two independent studies have demonstrated that treatment of C57BL/6 mice with anti-CD1d antibody enhances survival rates during CLP-induced sepsis [11,12], suggesting that NKT-cell-mediated promotion of sepsis depends on an interaction between CD1d and TCRs of NKT cells. In contrast, Etogo et al found that CD1d −/− mice did not exhibit improved survival in CLP-induced sepsis [10].…”
Section: Introductionsupporting
confidence: 68%
“…Additional depletion of NK cells by antiasialoGM1 antibody conferred complete resistance to septic mortality and was associated with diminished pro-inflammatory cytokine synthesis and secretion [45]. Similarly, Ja18 -/-mice were used to show that iNKT cell deficiency significantly decreased septic mortality and ameliorated the systemic proinflammatory response [46]. Despite contradictory findings on the relative contribution of iNKT cells to a Th1 or Th2 response, these results consistently implicate a detrimental effect of NKT cell activation in polymicrobial sepsis.…”
Section: Polymicrobial Sepsismentioning
confidence: 89%
“…Mice lacking type I NKT cells had lower levels of circulating gamma interferon (IFN-␥) and TNF-␣ and increased survival in the generalized Shwartzman reaction (20). Studies of polymicrobial septic shock provide divergent data; J␣18-deficient C57BL/6J mice lacking type I NKT cells showed an increased survival level and decreased levels of proinflammatory cytokines in the serum (21), while another study found that CD1d-deficient mice lacking all NKT cells did not differ from WT mice in septic mortality and induction of proinflammatory cytokines (37). In the S. aureus model of sepsis studied here, despite the activation of type I NKT cells by the bacterial injection, there was no significant difference in mortality rate in mice lacking type I NKT cells (J␣18 Ϫ/Ϫ ) or in CD1d-deficient mice compared to their heterozygote littermates.…”
Section: Figmentioning
confidence: 99%
“…Initial studies pointed to a detrimental role of NKT cells in sepsis by magnifying damage and increasing mortality (20)(21)(22)(23)(24). However, those studies either did not discriminate between type I and type II NKT cells (22)(23)(24) or focused exclusively on type I cells (20,21).…”
mentioning
confidence: 99%
See 1 more Smart Citation